Efficacy, safety, and cost-effectiveness of pegylated PEG-rhg-CSF in pediatric patients receiving high-intensity chemotherapy: results from a phase II study - Huang, Junting; Zhu, Jia; Jiang, Lian; Xu, Jiaqian; Lin, Xiheng; Chang, Jian; Zhang, Xiaohong; Lu, Suying; Sun, Feifei; Wang, Juan; Que, Yi; Ye, Zhonglv; et al. (Frontiers in Pharmacology, 2024)
Background High-intensity chemotherapy can cause life-threatening complications in pediatric patients. Therefore, this study investigated safety and efficacy of long-acting pegylated recombinant human granulocyte colony-stimulating factor (PEG-rhG-CSF; Jinyouli®) in children undergoing high-intensity chemotherapy. Methods Treatment-naive patients received post-chemotherapy PEG-rhG-CSF as primary prophylaxis for two cycles. The primary endpoints were drug-related adverse events (AEs) and bone pain scores. Secondary endpoints included grade 3–4 neutropenia, duration of neutropenia recovery, absolute neutrophil count changes, febrile neutropenia (FN), reduced chemotherapy intensity, antibiotic usage, and AE severity. The cost-effectiveness of PEG-rhG-CSF was compared with that of rhG-CSF (Ruibai®). Results Here, 307 and 288 patients underwent one and two PEG-rhG-CSF cycles, respectively. Ninety-one patients experienced drug-related AEs, primarily bone pain (12.7%). Moreover, Grade 3–4 neutropenia and FN were observed. Median FN durations were 3.0 days in both cycles. No drug-related delays were observed during chemotherapy. One patient experienced grade 4 neutropenia-induced reduction in chemotherapy intensity during cycle 2. In total, 138 patients received antibiotics. PEG-rhG-CSF exhibited superior cost-effectiveness compared to rhG-CSF. Conclusion Our findings indicate that PEG-rhG-CSF is safe, efficient, and cost-effective in pediatric patients undergoing high-intensity chemotherapy, providing preliminary evidence warranting further randomized controlled trials.